2019
DOI: 10.1177/0258042x18812582
|View full text |Cite
|
Sign up to set email alerts
|

Do Firm- and Board-specific Characteristics Corroborate Underpricing? A Study on the Indian IPOs

Abstract: The present research article is an attempt to add something new and revalidate the influence of already existing corporate governance dimensions related to the board of directors on listing-day performance of the Indian initial public offering (IPO) firms measured through underpricing. Like other emerging market economies, firms in the Indian economy are also characterized by concentrated ownership held by an owner or a promoter in the context of the Indian corporate environment. In the backdrop of this concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A typical IPO launch process can take around 6–12 months. On the US market, once a company reaches a preliminary understanding with its underwriters, the IPO process starts in full force, followed by a “quiet period” during which the company is subject to Securities and Exchange Commission guidelines regarding the publication of information not contained in its prospectus (Anand and Singh, 2019). However, Brazilian firms are allowed to promote business and disclose information regarding its value both before and after registering the IPO prospectus.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A typical IPO launch process can take around 6–12 months. On the US market, once a company reaches a preliminary understanding with its underwriters, the IPO process starts in full force, followed by a “quiet period” during which the company is subject to Securities and Exchange Commission guidelines regarding the publication of information not contained in its prospectus (Anand and Singh, 2019). However, Brazilian firms are allowed to promote business and disclose information regarding its value both before and after registering the IPO prospectus.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The optimal board size for SMEs is still an object of debate, with few studies emphasizing the advantages of larger board sizes and other studies elaborating on smaller board sizes. In the IPO context, the unconvincing nature of the relationship between board size and underpricing calls for further discussion (Li and Naughton, 2007; Bédard et al , 2008; Mitchell Van der Zahn et al , 2008; Mnif, 2009; Hearn, 2011; Darmadi and Gunawan, 2013; Handa and Singh, 2017; Anand and Singh, 2019). Regarding board independence, it is generally inferred that independent directors enhance board quality through effective monitoring and exchange of valuable knowledge and technical guidance, supporting an organisation’s development.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…However, inconclusive evidence concerning underpricing calls for further investigation of this variable (Bédard et al , 2008; Chahine and Filatotchev, 2008; Mitchell Van der Zahn et al , 2008; Mnif, 2009; Yatim, 2011; Lin and Chuang, 2011; Darmadi and Gunawan, 2013; Handa and Singh, 2017; Alvarez-Otero and Lopez-Iturriaga, 2018). Some authors have explored the role of board committees (Hearn, 2011; Handa and Singh, 2017; Anand and Singh, 2019) in various settings and with multiple performance measures, with weak conclusions, which call for further debate. With regards to ownership concentration, Ekkayokkaya and Pengniti (2012) have found that large shareholders on the board act as a double-edged sword: on the one hand, they assist in addressing agency issues; on the other hand, they aggravate expropriation risks, particularly in economies with weaker institutional regimes.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, complementing the literature skewed with the developed economies, particularly US and the European market and China in the context of emerging economies, the study explores the traits of sound IPOs in the Indian market. Indian IPO market captured researchers' tractions post-1995, with listing returns (Babu and Dsouza, 2021;Maheshwari and Kumar, 2022), under-pricing (Ghosh, 2005;Ranganathan and Saraogi, 2021), earning-management (Mangala and Dhanda, 2021;Pandey and Pattanayak, 2022), anchor investors (Kumar and Sahoo, 2021;Sahoo, 2017), allocation (Bhattacharya et al, 2020;Seth et al, 2019), board diversity and other qualitative factors (Agarwal and Vyas, 2022;Anand and Singh, 2019) as the prime focus. To the finest of the authors' information, this is the first Indian study examining the IPO performance and post-listing market sustainability determinants.…”
Section: Introductionmentioning
confidence: 99%